A relação com o saber de alunos de um curso normal de nível médio - Rebel, Sandra Maria Cavalcanti (2007)
In this dissertation we will discuss the French researcher Bernard Charlot s theory. My main goal is to encourage further critical thinking on specific issues of Mr. Charlot s theory, especially those that are closely related to a teacher s professional methods. Students observations are used throughout the text to illustrate the theory s main principles. On those remarks we observe the different meanings that the learning experience can have and the many expectations teenagers have from the schools. I ll also discuss the value of "Singularity of schooling histories" - considering each student s unique school backgrounds in order to fully understand the student s relationship to knowledge. The article also demonstrates the importance of a teacher s approach based on regular student feedback; hearing and understanding what students think of the school, the teachers and the process of learning itself. The essay also shows the importance of selfanalysis; teachers observing themselves and their techniques in order to reassure they are facilitating a mobilization of the student in the school and in the relation to the school. Ultimately, I ll be showing how vital is to fully understand a student s behavior at school from the relationship to knowledge standpoint.